A Study of a Certain Subclass of Hurwitz-Lerch-Zeta Function Related to a Linear Operator. (30th September 2013) - Ghanim, F.
Abstract : By using a linear operator with Hurwitz-Lerch-Zeta function, which is defined here by means of the Hadamard product (or convolution), the author investigates interesting properties of certain subclasses of meromorphically univalent functions in the punctured unit disk U * .